Порівняльна оцінка жирнокислотного складу олій насіння форм та сортів тифону, редьки олійної і рижію як перспективної сировини для отримання біодизелю - Блюм, Р.Я.; Бойчук, Ю.М.; Ємець, А.І.; Рахметова, С.О.; Блюм, Я.Б.; Рахметов, Д.Б. (Фактори експериментальної еволюції організмів, 2016)
Aim. Main aim of this research was a comparison of fatty acid composition for seed oils from of tyfon, oil radish and camelina breeding forms and varieties produced in Natl. Botanical Garden of Natl. Academy of Sciences of Ukraine. Methods. Biochemical analysis of oil content as well as chromatographic analysis of fatty acid composition of mentioned above species and their genotypes were conducted out. Results. On the basis of biochemical analysis of different breeding forms and varieties of tyfon (Brassica campestris f. biennis DC. × B. rapa L.) and oil radish (Raphanus var. oleifera sativus L.) maximal oil content in seed was calculated (up to 45.1% for tyfon and up to 42% – for oil radish). The best genotypes with optimal fatty acid composition for biodiesel production were identified. Basing on chromatographic analysis of fatty acids of highly oil-containing false flax (Camelina sativa) genotypes (with oil content 42.6–43.9%), most optimal fatty acid composition for biodiesel production was identified in Peremoha variety and breeding forms ФЕОРЖЯФ-2 and ФЕОРЖЯФД. Conclusions. Respectively, the conclusion can be made, that accepting yield levels for biodiesel production the attention must be concentrated on such breeding varieties and varieties as Peremoha, ФЕОРЖЯФ-2 and ФЕОРЖЯФД (Camelina), Fitopal and ЕОТФВ (tyfon) and ЕОРДОФЛ-5 (oil radish). But accounting high level of linolenic acid (up to 38.3%) and other mono- and polyunsaturated fatty acids (up to 87.9%) false flax (Camelina) represents most appropriated species for industrial biodiesel production. Keywords: Brassicaceae, tyfon, oil radish, camelina, varieties, breeding forms, oil, fatty acids, biodiesel production.